2014
DOI: 10.15678/aoc.2014.1104
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Human Resource Management Practices on Employee Readiness for Change during Mergers and Acquisitions

Abstract: Embracing constant and continuous change is a necessity for business success. An organisation must be in a continuous state of change readiness. Researchers have confirmed that for organisational readiness, individual employees must also be open, prepared, and ready for change. Researchers and practitioners have both found employee readiness to be a critical factor in successful change efforts. This study presents the impact of employee perception of human resource management practices on employee readiness fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…By effective human capital, organizations will be able to grow in the face of market turbulence and critical challenges in the work-life. The second hypothesis has been empirically proven that there is a significant influence between HCE on RTC (Goksoy, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…By effective human capital, organizations will be able to grow in the face of market turbulence and critical challenges in the work-life. The second hypothesis has been empirically proven that there is a significant influence between HCE on RTC (Goksoy, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Several factors make up this competency. In order to act as an agent of change, extensive research suggests HR managers to have an understanding of the relevance associated with social capital and relationship management, ethical leadership, treating the affected employee as an internal stakeholder, developing consensus among the affected stakeholders, and the role communication plays within the process [26,[28][29][30][31][32][33][34][35]. This mindset has been identified by Salamzadeh, et al [2], who found that more attention should be paid to human resource practices for improved corporate entrepreneurship.…”
Section: Hr Department As Agent Of Changementioning
confidence: 99%
“…There are several crucial reasons to enroll internal stakeholders in communications regarding changes. We believe that the most pertinent to this paper include involving those affected in the implementation process [28,33]; maintaining the trust of those affected [30,34] involving HR in meaningful ways (Maheshwari & Vohra, 2015;Teo, 2002); and generating transparent disclosure to all affected parties [32].…”
Section: Hr Strategy One: Enlist Internal Stakeholders By Consistently Applying Past Relevant Experience Enroll Stakeholdersmentioning
confidence: 99%
See 2 more Smart Citations